Growth expectations, undue optimism, and short-run fluctuations - Enders, Zeno; Kleemann, Michael; Müller, Gernot J. (The review of economics and statistics, 2021)
This paper proposes a two-step procedure in order to identify belief shocks—shocks to expectations about the current state of the economy. First, we use the Survey of Professional Forecasters to measure nowcast errors about contemporaneous output growth. Second, we extract belief shocks from nowcast errors, once by regressing them on existing measures of structural shocks and once by imposing sign restrictions on a VAR model. Using both approaches, we find that belief shocks trigger similar adjustment dynamics and a high degree of co-movement across macroeconomic variables. Belief shocks account for about onethird of short-run output fluctuations.